2021
DOI: 10.1002/pmic.202000221
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase‐2, RNA‐binding proteins and mitochondrial proteins selectively traffic to MDCK cell‐derived microvesicles following H‐Ras‐induced epithelial–mesenchymal transition

Abstract: Epithelial-mesenchymal transition (EMT) describes an evolutionary conserved morphogenic process defined by loss of epithelial characteristics and acquisition of mesenchymal phenotype, and altered patterns of intercellular communication, leading to functional changes in cell migration and invasion. In this regard, we have previously reported that oncogenic H-Ras induced EMT in Madin-Darby Canine Kidney (MDCK) cells (21D1 cells) trigger changes in the protein distribution pattern in cells, exosomes, and soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Proteomic analyses of the secretomes of MDCK and 21D1 cells showed the remodeling of extracellular matrix (ECM) proteins, including decreased levels of basic membrane components (e.g., collagen type IV) and proteases (e.g., matrix metalloproteinase 1 (MMP-1)) 60 . Proteomic analyses of 21D1 cell-derived exosomes showed a decrease in some epithelial biomarkers (e.g., E-cadherin and EpCAM) but an increase in mesenchymal biomarkers (e.g., vimentin) and proteinases (e.g., MMP-1) 61 . Therefore, a thorough recognition of the function of exosomal proteins in EMT is needed.…”
Section: The Effect Of Exosomal Protein Cargo On Cancer Biologymentioning
confidence: 95%
“…Proteomic analyses of the secretomes of MDCK and 21D1 cells showed the remodeling of extracellular matrix (ECM) proteins, including decreased levels of basic membrane components (e.g., collagen type IV) and proteases (e.g., matrix metalloproteinase 1 (MMP-1)) 60 . Proteomic analyses of 21D1 cell-derived exosomes showed a decrease in some epithelial biomarkers (e.g., E-cadherin and EpCAM) but an increase in mesenchymal biomarkers (e.g., vimentin) and proteinases (e.g., MMP-1) 61 . Therefore, a thorough recognition of the function of exosomal proteins in EMT is needed.…”
Section: The Effect Of Exosomal Protein Cargo On Cancer Biologymentioning
confidence: 95%
“…This was dependent on the simultaneous transfer of fibronectin, which is cross-linked within the microvesicle and is required for fibroblast activation [ 245 , 250 ]. The enrichment of TG2 in MVs following h-RAS-induced EMT provides a potential link between EVs and the ability of TG2 to mediate EMT and subsequent invasive behaviour [ 251 ].…”
Section: Tg2—a Stage-specific Cancer Targetmentioning
confidence: 99%
“…Besides, MTDH-dependent anoikis resistance is activated by the PI3K/Akt pathway, and anoikis resistance is obtained by inhibiting caspase-3 activation and activating CXCR4 expression levels (Zhou et al, 2014), targeting MTDH can limit PDAC metastasis (Suzuki et al, 2017). Recently, a study suggested that FN1 promotes cellular aggregate formation conferring anoikis resistance to tumor cells (Han et al, 2021), and that pretreatment of exosomes with anti-FN1 antibodies attenuates the invasive ability of fibroblasts (Shafiq et al, 2021). PRDX4 is overexpressed in a variety of tumor tissues (Jia et al, 2019), and inhibits anoikis resistance through the β-catenin/ ID2 pathway, thereby promoting the growth and metastasis of hepatocellular carcinoma cells (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%